Market Survey in Customer Purchasing for Entrepreneurs’ Resilience: An Analysis of Garment and Textile Industry - Mohamad, Arifha; Isa, Anis Munira; Abu Seman, Noor Aslinda; Mohd Adi, Mohd Nazir; Jusoh, Nur Aniza Quantaniah; Rashid, Umi Kartini (JBS Nexus, 2024)
This market survey analyzes customer purchasing behavior in the garment and textile industry, focusing on how entrepreneurs can build resilience in their operations. The study surveyed 189 fashion customers aged 18 to 45 in Jeli, Kelantan, to determine key factors influencing purchasing decisions, including spending patterns, purchasing frequency, and considerations such as price, design, and fabric. The results indicate that a majority of respondents prioritize affordability, with 56.7% spending RM100 or below on clothes monthly and 53.3% influenced by sales and promotions. Social media plays a significant role in trend discovery, with 90% of respondents using these platforms to stay updated on fashion trends. Most consumers still prefer physical stores for purchases, with 63.3% favoring this option. When selecting clothes, design (36.7%) and price (30%) are the most important factors. This study provides insights for garment and textile entrepreneurs on the importance of aligning their business strategies with consumer preferences for affordability, fashion trends, and the convenience of physical shopping experiences.